Metal pollution of low-mass Population III stars through accretion of interstellar objects like 'Oumuamua. (3rd July 2018) - Tanikawa, Ataru; Suzuki, Takeru K; Doi, Yasuo
Abstract: We calculate the accretion mass of interstellar objects (ISOs) like 'Oumuamua on to low-mass Population III stars (Pop. III survivors), and estimate the surface pollution of Pop. III survivors. The ISO number density estimated from the discovery of 'Oumuamua is so high (∼0.2 au −3 ) that Pop. III survivors have chances of colliding with ISOs ≳ 10 5 times per 1 Gyr. 'Oumuamua itself would be sublimated near Pop. III survivors, since its size is small; ∼100 m. However, ISOs with size ≳3 km would reach the Pop. III survivor surfaces. Supposing an ISO cumulative number density with size larger than D is n ∝ D −α, Pop. III survivors can accrete ISO mass ≳10 −16 M ⊙, or ISO iron mass ≳10 −17 M ⊙, if α < 4. This iron mass is larger than the accretion mass of interstellar medium (ISM) by several orders of magnitude. Taking into account material mixing in the convection zone of Pop. III survivors, we find that their surface pollution is typically [Fe/H] ≲ −8 in most cases; however, the surface pollution of Pop. III survivors with 0.8 M ⊙ can be [Fe/H] ≳ −6 because of the very shallow convective layer. If we consider Pop. III survivors located at the Galactocentric distance of 8 kpc, the dependence of the metal pollution is as follows. If α > 4, Pop. III survivors have no chance at colliding with ISOs with D ≳ 3 km, and remain metal-free. If 3 < α < 4, Pop. III survivors would be most polluted by ISOs up to [Fe/H] ∼ −7. If α < 3 up to D ∼ 10 km, Pop. III survivors could hide in metal-poor stars so far discovered. Pop. III survivors would be more polluted with decreasing Galactocentric distance. Although the metal pollution depends on α and the Galactocentric distance, we first show the importance of ISOs for the metal pollution of Pop. III survivors.